Comparative investigation of the Ni and the Fe effect on the structure and mechanical response of a WC-W-Ni hardmetal obtained by infiltration. (February 2019) - Bouchafaa, H.; Miroud, D.; Mato, S.; Boutaghou, Z.; Cheniti, B.; Pérez, F.J.; Alcalá, G.
Abstract: In the present work, and in order to enhance the efficiency of drilling tools for the oil and gas industry, the influence and performance of Ni and Fe during spontaneous infiltration on a WC-W-Ni composite material mechanical behaviour was addressed. Solid-state activity of Fe and Ni during infiltration exhibits partial dissolution in the metallic binder. The chemical affinity between Fe and Ni, provided by the Fe powder and the binder respectively, derived on the formation of the (Fe, Ni) solid solution and FeNi3 intermetallic precipitates in the particle/matrix diffusion region, with a hardness (12 GPa) close to that of WC and high elastic modulus (230 GPa). Furthermore, the diffusion of Fe to the matrix leads to the formation of sub-micrometer precipitates of α-Fe with some (Ni, Mn) in solid solution and of Ni3 Sn with a small amount of Cu dissolved, driving to an increase of about 30% in its elastic modulus, and without appreciable effect in the hardness observed. Highlights: The optimal experimental infiltration parameters for infiltration were determined by Differential Thermal Analysis. The presence of Fe particles during infiltration leads to the formation of hard and stiff phases such as FeNi3, increasing hardness of the Fe particles in about 350%. The CALPHAD simulation method allows identifying the Ni3 Sn and αFe precipitates produced in the matrix of the infiltrated Fe powder, which rise its elastic modulus about 40%. The almost complete dissolution of the Ni powder in the binder increases its hardness about 35%. The potential of Fe to replace Ni, either partially or completely, in the production of WC-W-Ni powder mixture infiltrated with a Cu based alloy is addressed.